Pungutan Pajak Perdagangan Melalui Elektronik Antar Negara Berdasarkan Hukum Perpajakan Di Indonesia - Fuzzy Kartika Candra Dewi; Muhammad Yasir (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to determine the applicable taxation arrangements in Indonesia for e-commerce or e-commerce business actors between countries. Specifically, this study tries to explore the content of rules to harmonize regulations with rules relating to e-commerce. In addition, this study also examines specifically the rules that can be imposed on e-commerce businesses, tax arrangements, qualifications of tax subjects, and tax objects that can be withdrawn from e-commerce business actors between countries. This research is a library research through statutory approach. The results showed that Indonesia already has general rules regarding taxes for foreign tax subjects, so that if there is an inter-state e-commerce business actor having sources originating from the Indonesian state, then the inter-state e-commerce business actor can be said to be a taxpayer abroad with qualifications article 26 of the Republic of Indonesia Law No. 36/2008 concerning the Fourth Amendment to Law No. 7 of 1983 concerning Income Taxes.Keywords: e-commerce tax, e-commerce between countries